Platform motion minimization using model predictive control of a floating offshore wind turbine. Issue 5 (July 2021) - Shah, Kamran Ali; Li, Ye; Nagamune, Ryozo; Zhou, Yarong; Ur Rehman, Waheed
Highlights: System dynamics model of a floating offshore wind turbine is proposed. Simplified model-based MPC is designed to deal with platform motions in the presence of realistic wind and waves. MPC is compared with the baseline PI and LQI controller with extensice discussion. Abstract: Wind turbines are installed offshore with the assistance of a floating platform to help meet the world's increasing energy needs. However, the incident wind and extra incident wave disturbances have an impact on the performance and operation of the floating offshore wind turbine (FOWT) in comparison to bottom-fixed wind turbines. In this paper, model predictive control (MPC) is utilized to overcome the limitation caused by platform motion. Due to the ease of control synthesis, the MPC is developed using a simplified model instead of high fidelity simulation model. The performance of the controller is verified in the presence of realistic wind and wave disturbances. The study demonstrates the effectiveness of MPC in reducing platform motions and rotor/generator speed regulation of FOWTs.